Seismicity along the Mohns—Knipovich Ridge Bend and its correlation to ridge spreading rate - Pirli, Myrto; Schweitzer, Johannes; Faleide, Jan Inge; Grad, Marek; Guterch, Aleksander; Krüger, Frank; Mjelde, Rolf; Schmidt-Aursch, Mechita (Journal of Geodynamics, 2018)
The study presents eleven months of seismicity at the Mohns-Knipovich Ridge Bend area, northern North Atlantic, based mainly on observations from a combined land-based and ocean-bottom regional seismic network. The achieved epicentre accuracy allows to associate the events with major volcanic centres and order-2 ridge segments. The use of event detectors enables a more complete overview of the seismic activity, permitting the identification of discrete episodes. Their morphological and statistical characteristics provide valuable insight into their nature and origin, i.e., whether they are associated with tectonic or volcanic processes. The geographic distribution of the seismicity reflects the different environments met within the study region, slow-spreading segments being overall more seismically active than segments spreading at ultra-slow rates and event magnitudes decreasing with increasing ridge obliquity, probably as a result of rupture scaling.